Analisis Literasi Dasar terhadap Keterampilan Membaca dan Menulis Peserta Didik Kelas II SD - Safitri, Ratna; Prahastiwi, Eka Danik (Lembaga Yasin AlSys, 2026)
Low reading and writing literacy skills among early-grade elementary school students remain an important problem in the learning process. This study aims to analyze the condition of basic literacy in relation to the reading and writing skills of second-grade students at SD Negeri Kembang Pacitan. This study employed a qualitative approach with a case study design. The research subjects consisted of 13 second-grade students. Data were collected through observation, semi-structured interviews, and documentation and were then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results showed that most students still experienced difficulties in beginning reading and writing. In reading skills, the majority of students were in the less fluent category, whereas in writing skills the majority were in the adequate category. The difficulties identified included letter recognition, reading fluency, the use of capital letters, spelling, and handwriting neatness. Factors influencing students’ literacy skills included low reading interest, lack of parental assistance, limited reading materials, and learning that remained conventional. The conclusion of this study affirms that the reading and writing literacy skills of second-grade students still need to be improved through more innovative learning strategies and support from the family environment. The implications of this study provide a basis for teachers and schools in developing more effective literacy programs to improve elementary school students’ reading and writing skills.